Integrating fish scale and bone isotopic compositions for 'deep time' retrospective studies. (September 2020) - Guiry, Eric J.; Hunt, Brian P.V.
Abstract: Isotopic studies of archived fish scales have tremendous potential to develop long-term retrospectives that provide important insights into how humans have altered aquatic ecosystems. However, fish specimens in museum archives and other repositories typically date to time periods when the impacts of industrial societies may have already caused profound environmental changes. Archaeological fish bones offer an opportunity to bridge this key temporal gap by providing samples spanning from the recent past to as far back as the Pleistocene. Collagen is the primary protein component of both fish scale and bone, but the comparability of isotopic compositions from these tissues has not been established experimentally. To lay the framework for integrating isotopic datasets from these tissues, we compare δ 13 C and δ 15 N of bone and scale collagen, as well as other tissues, from fish with life-time controlled diets. Results show that while there is no difference in δ 13 C between scale and bone collagen, there may be a very slight but meaningful inter-tissue offset in δ 15 N (<0.3‰). We discuss potential sources of δ 15 N variation in scale and bone collagen measurements. Because there is no difference in scale and bone δ 13 C, and the observed offset in δ 15 N is very small (less than analytical uncertainty in many studies), our findings demonstrate that collagen isotopic compositions from these tissues should be directly comparable when integrating datasets from modern and ancient samples to build more powerful, millennium-scale isotopic times series. In linking isotopic compositions of collagen from modern, historical (scales), and archaeological (bones) fish, our findings open the way for more nuanced contextualization of how ecosystems functioned prior to large-scale exploitation and how they have responded to mounting anthropogenic pressures in the intervening centuries. Highlights: Scale/bone collagen isotope compositions are directly comparable in most studies. Millennium-scale isotopic retrospectives possible by combining scale and bone. Non-collagenous protein contamination may be an issue for modern collagen extracts. Modern bone collagen extraction may benefit from NaOH pre treatment. Isotopic inter-tissue calibration studies should use animals with known diets.